Exploring the correlation between physicochemical properties of nanomaterials and their genotoxic effects in human cells - Louro, Henriqueta (2017)
Even though the use of nanomaterials is widespread, it is not clear to what extent they may impact the environment and human health. Recent studies have suggested that specific physicochemical properties of the NM may define their nano-bio interactions, thereby determining their toxic potential. The present work aimed at exploring correlations between the genotoxicity of two classes of nanomaterials, titanium dioxide nanomaterials (TiO2) and multi-walled carbon nanotubes (MWCNTs), and their specific properties. Human lymphocytes and a pulmonary cell line were exposed to several TiO2 and MWCNT, respectively, and their genotoxicity was assessed by the cytokinesis-block micronucleus (MN) assay. Whereas various concentrations of the two rutile TiO2 were able to increase significantly the MN frequencies, the anatase produced a single significant data point and the rutile/anatase yielded negative results; none of the TiO2 produced a dose-response relationship. On the other hand, two MWCNTs significantly induced the MN frequency with a dose-response relationship, while the remaining did not. Correlation analysis evidenced a strong significant positive correlation between the frequency of MN and the diameter of the TiO2 while for MWCNT the strongest association was with aspect ratio. In conclusion, although further investigation with larger panels of nanomaterials is necessary, these findings illustrate the importance of exploring the properties that contribute most for NMs biological interactions. Such knowledge-base may enable grouping strategies for safety assessment and the development of safe-by-design approaches.